WWP2 and its association with PTEN in endometrial cancer - Aine E. Clements; Veronica Bravo; Christopher Koivisto; David E. Cohn; Gustavo Leone (Elsevier, 2015)
We wished to determine if WWP2 gene expression and PTEN protein levels inversely correlate in human endometrial cancer tissues. Fifty-one endometrioid endometrial tumors and five normal endometrial controls were available for analysis. PTEN protein levels were assessed by immunohistochemistry (IHC). WWP2 and PTEN gene expression were quantitated by RT PCR. Clinical and pathologic information was collected by chart review. We found that in tumors with low PTEN protein but normal mRNA expression there were significantly higher levels of WWP2 expression (p = 0.0017). Increased WWP2 expression was not associated with clinical prognostic factors including lymphovascular space invasion, ≥50% myometrial invasion, grade, stage or recurrence. WWP2 expression was not different statistically between tumors and normal controls (p = NS). Therefore, in this cohort, tumors with low PTEN protein but normal mRNA expression had elevated levels of WWP2 expression. This suggests that WWP2 may be playing a role in PTEN degradation in endometrial cancer.